"Preparation of fast disintegrating tablets of Ondansetron Hydrochloride " - استانبولي, مقبولة; تميم حماد,; وسيم عبد الواحد, (Latakia University Journal -Medical Sciences Series, 2023)
This research aims to prepare Ondansetron Hydrochloride orally disintegrating tablets. Direct compression and lyophilization methods were used in the preparation. For the direct compression method, glucose was used as diluent with different disintigrants such as: Kollidon CL, Ac-di-sol at different concentrations. As for the lyophilization method, different binding agents were used such as: gelatin and PVP K30 with different concentrations of mannitol as building agents. Tablets (F9) containing 20 mg Kollidon CL with 20 mg Ac-di-sol showed the lowest disintegration time of 30 seconds compared to the other formulations prepared by direct compression method, while the lyophilizate FDTs (L6) containing 60% mannitol and both gelatin and PVP K30 as a binder was the best formulation prepared by lyophilization method, it had a good external appearance and disintegrated within 12 seconds. Oral lyophilized FDTs showed a faster rate of drug release compared to the direct compression FDTs, releasing 77% of ondansetron hydrochloride within the first two minutes, compared to 43% for the direct compressed FDTs (f1 >15 , f2 < 50).